Auditoria de enfermagem: construção e aplicação de indicadores de qualidade no processo de acreditação - Vigna, Cinthia Prates (2016)
Introduction: The search for Accreditation is a growing reality in hospitals and recently in Health Plan Operators (OPS), through the program established by Normative Resolution 277. The use of indicators is one of the most used forms of assessment quality in health services. Objectives: To build and measure quality indicators for nursing audit in the accreditation process. Propose actions to improve the network of hospitals and the audit service of the OPS. Compare the use of lancing technologies and securing peripheral intravenous catheter (CIP) and the length of time consumption and cost. Update and analyze the impact of equipo exchange protocol used in intravenous therapy based on best practices. Build and measure the quality indicator related to central venous catheter. Method: a descriptive exploratory study, quantitative and retrospective itself (2013), conducted in six hospitals linked to an OPS in which the data were obtained from the Nursing Audit service. They were constructed and validated care indicators and management by the audit team and quality OPS for compliance with the dimensions 1 and 2 of RN 277. Results: From the OPS Accreditation process indexes were created and performed protocol update. of service quality indicators, peripheral intravenous catheter time, care incidents related to central venous catheter and equipo exchange time protocol infusion based on scientific evidence, have been based in "second dimension" which It comes to the quality and dynamic performance of the hospital network that provides services to OPS. Quality indicators management were drawn from the "size 1" which evaluates the most common business processes and critical of the audit service. The equipo exchange protocol deployed in hospitals showed a reduction in consumption and cost, and improved safety to the customer. Subsequently, assistance with improvement proposals were presented to hospitals and management to OPS. Conclusion: This study showed the building, measuring six indicators of quality care, four in management and material consumption protocol update the audit nursing. In addition, proposals to hospitals focused on patient safety assurance and the audit service of the OPS to improve the processes and results were presented. There was a new performance audit of nursing through quality indicators in order to encourage continuous improvement of the assistance provided by hospitals and the management of the OPS audit service. It also contributes to the auditor nurse seek new practices, assuming his role as responsible for the pursuit of customer service quality.